Why New Drugs, Treatments, and Medical Devices Still Needs to be Tested Clinically Before Making it Available in the Market? - Naiya, Patel (Journal of Neurological Research And Therapy, 2019)
Objective Testing a new drug, treatment, and medical device clinically is critically important before prescribing it to patient. Not determining the drug’s safety and efficacy through clinical trials might impose life threatening outcomes on its consumers. The research paper describes the critical factors associated for testing any new drugs clinically, as limited research is performed in this field of public health. Study Design A qualitative systematic literature review was performed by mining relevant original peer reviewed research papers as well as some online resources like MedlinePlus due to limited availability of studies on such critical topic. Methods The databases used were Web of Sciences core collection, PubMed, Google scholar. The keywords used to search research papers were “clinical trials”, “testing new drugs”, “history of testing drugs”, “evidence-based medicine”. Conclusion Drugs which are prescribed to critical target population like pregnant women and children should be more often clinically tested if possible as majority of them are available in the market without Food and Drug Administration (FDA) approval. The abusive potential of any new drug could end up taking lives of innocent individuals. More evidence-based medicine can help translate research results on a heterogeneous population efficiently.
Keywords: clinical trials; new drug testing; evidence-based medicine; public health